(3Pjd GdCeGdjs - (3CHh Ydj GdbGdj , ESeGYjd Hf GdbGSe Hf YHOhf Hf gGQhf Hf YjSi Hf eMeO Hf SdeGf, CHh Ydj,J (B356 (3g` s ((3eMeO Hf EHQGgje Hf CMeO Hf SYjO Hf SYO s)
(3ChdgG (B:s
(3Chd GdRjGOI aj GdCeGdj, GdeYQhaI HGdPjd, JCdja CHj Ydj ESeGYjd Hf GdbGSe GdHZOGOjbGd CHhYdj(B: (3MOKfG CHhHcQ QMeg Gddg bGd GdQjGTj s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde bGd(B: (3ef eWQ JeJ GdRjGOI dCHj Ydj ESeGYjd Hf GdbGSe GdHZOGOj QMeg Gddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B136 (3L (B- (3U(B167 (3Hs
(3GfXQg eY GdCeGdjs
(3fSNI YJjbI LOkG hfajSIs
(3hojdGMX Cf GdYfhGf hVY bHd HOA GdcJGH HCQHY UaMGJs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs